2000
DOI: 10.1021/bi0011577
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the RNA-Editing Reaction of ADAR2 with Structural and Fluorescent Analogues of the GluR-B R/G Editing Site

Abstract: ADARs are adenosine deaminases responsible for RNA editing reactions that occur in eukaryotic pre-mRNAs, including the pre-mRNAs of glutamate and serotonin receptors. Here we describe the generation and analysis of synthetic ADAR2 substrates that differ in structure around an RNA editing site. We find that five base pairs of duplex secondary structure 5' to the editing site increase the single turnover rate constant for deamination 17-39-fold when compared to substrates lacking this structure. ADAR2 deaminates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 32 publications
9
99
0
Order By: Relevance
“…In the case of the GluR-B R/G derivative, an A:U base pair at the editing site did not significantly alter ADAR2-catalyzed editing+ This is consistent with a recent report (Stephens et al+, 2000) where only a very modest decrease in the extent of deamination by ADAR2 was observed in vitro when the same mutation in the wild-type R/G site was tested+ Based on this finding, the authors concluded that the identity of the base opposing the edited adenosine exerts a relatively minor effect on editing+ However, if the investigators had tested ADAR1 with the same mutant or ADAR2 with a GluR-B R/G mutant that contained an A:G mismatch at the editing site, they would likely have observed a more severe effect+…”
Section: Discussionsupporting
confidence: 91%
“…In the case of the GluR-B R/G derivative, an A:U base pair at the editing site did not significantly alter ADAR2-catalyzed editing+ This is consistent with a recent report (Stephens et al+, 2000) where only a very modest decrease in the extent of deamination by ADAR2 was observed in vitro when the same mutation in the wild-type R/G site was tested+ Based on this finding, the authors concluded that the identity of the base opposing the edited adenosine exerts a relatively minor effect on editing+ However, if the investigators had tested ADAR1 with the same mutant or ADAR2 with a GluR-B R/G mutant that contained an A:G mismatch at the editing site, they would likely have observed a more severe effect+…”
Section: Discussionsupporting
confidence: 91%
“…We used phosphoramidite 7 and the appropriate deprotection conditions to prepare mimics of the glutamate receptor B-subunit (GluR-B) pre-mRNA near the R/G editing site ( Figure 4A). 17 We chose initially to analyze the effect 8-azanebularine has on the ADAR2 RNA binding affinity using a deletion mutant of the enzyme lacking dsRBM I (ADAR2 216-711 ) ( Figure 4B). We refer to this protein as R-D because it contains one dsRBM and the Deaminase domain.…”
Section: Resultsmentioning
confidence: 99%
“…Although subtle determinants of ADAR specificity have been identified in the DRBMs (46), the primary determinants of ADAR site specificity are thought to reside in the characteristics of their dsRNA substrates (38,47). Structural selectivity of ADARs for a particular adenosine in the duplex is thought to be imparted by the pattern of bulges and base-pairing regions in the dsRNA, combined with the overall thermodynamic stability of the RNA (20,21,46,48). According to observations made using artificial substrates, internal loops of greater than six nucleotides define subdomains of ADAR action (22).…”
Section: Discussionmentioning
confidence: 99%
“…A similar base-flipping strategy has been implicated for ADAR2 function in which the DRBM not only plays a role in the recognition of potential ADAR2 sites, but also an additional role in rendering the nucleotides around the targeted adenosine more conformationally flexible, thus lowering the activation energy for base flipping (19,48). More recent studies have demonstrated that the identity of nucleotides surrounding the targeted adenosine moiety can affect the efficiency of editing, possibly by altering whether the targeted adenosine is stacked in the RNA helix (50), suggesting that local sequences surrounding the edited adenosine moiety can affect its ability to be flipped out of the helix during catalysis.…”
Section: Discussionmentioning
confidence: 99%